Handicraft process, aesthetic characteristics, and design applications of molten metal inlaid in wood for home furnishings - Tao, Xin; Wu, Shuangshuang; Wei, Peng; Xu, Wei (Bioresources, 2025)
The inlaying of molten metal into artificial or natural wood cracks represents an innovative combination of metal and wood. After cooling and solidifying, a unique texture is formed, offering a rich aesthetic experience rooted in its intricate decorative texture. This study systematically summarizes the process steps of molten metal inlaid in wood, including material selection, pretreatment, casting, cooling, and sanding. It elaborates on the aesthetic characteristics and decorative potential of this novel material through three aspects, including visual expression, tactile difference, and cultural value. Selected design cases of molten metal inlaid in wood for home furnishings are analyzed to assess the product design feasibility through the lens of craft aesthetics. The research further provides a guiding direction for its design application in household products.